A novel integrated approach for monitoring drought stress in an aeolian desertification area using Vegetation Drought Status Index - Zhixin Zhao; Qi Liu; Aidi Huo; Yuxiang Cheng; Wenke Guan; EL-Sayed Abuarab Mohamed; Ali Mokhtar; Ahmed Elbeltagi (Water Supply, 2023)
Drought is a costly natural disaster. The accuracy and applicability of different drought indexes in drought monitoring at different research areas are also different. Based on remote sensing (RS) and geographic information system technology, we propose a new RS-based drought index, Vegetation Drought Status Index (VDSI), for agricultural drought monitoring in both arid and humid regions using multi-sensor data. This index combines the Normalized Difference Vegetation Index (NDVI) data from Moderate Resolution Imaging Spectroradiometer (MODIS) sensor and data from 81 verification points regarding the in situ soil drought status. The model was applied to drought monitoring in Xinjiang Uygur Autonomous Region of China. Based on the comprehensive influence of water absorption on the reflectance spectrum of vegetation and soil, the reflectance of soil in MODIS bands B6 and B7 is generally higher than that of vegetation, so the model can directly obtain the surface soil moisture index. The correlation analysis (R2 > 0.79) was valid; the change trends were the same; i.e., VDSI is a reliable referential index for agricultural drought monitoring. HIGHLIGHTS A new drought index based on remote sensing – Vegetation Drought State Index (VDSI) was proposed.; The model can directly obtain the surface soil moisture index.; The results are applicable to agricultural drought monitoring in arid and humid regions.;